2004
DOI: 10.1177/1463499604040845
|View full text |Cite
|
Sign up to set email alerts
|

Anthropology and Genocide in the Balkans

Abstract: This article examines scholarly discourse on the wars in the former Yugoslavia. It focuses on relativistic arguments put forward by anthropologists and shows how such accounts mask and elide central historical realities of the conflict. Relativistic accounts of serious modern conflicts often mirror and offer legitimation to the accounts put forth by perpetrators. In this case, several leading accounts of the wars in the former Yugoslavia display a strong affinity to those asserted by Serbian nationalists. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…From the organized and systematic nature of the mass rapes of women both in Bosnia and in Kosovo, many have concluded that these rapes were part of a larger Serbian campaign of genocide [139]. For many, the Serbs, with Bthe complicity of Serbian intellectuals^ [140], and sometimes with that of international networks of experts and institutions [141], were carrying out a policy of genocidal rape against other ethnic groups in former Yugoslavia.…”
Section: A Morphodynamic Approach To Mass Rapesmentioning
confidence: 99%
“…From the organized and systematic nature of the mass rapes of women both in Bosnia and in Kosovo, many have concluded that these rapes were part of a larger Serbian campaign of genocide [139]. For many, the Serbs, with Bthe complicity of Serbian intellectuals^ [140], and sometimes with that of international networks of experts and institutions [141], were carrying out a policy of genocidal rape against other ethnic groups in former Yugoslavia.…”
Section: A Morphodynamic Approach To Mass Rapesmentioning
confidence: 99%
“…During the 1990's, while the worst atrocities were taking place in Bosnia, political leaders avoided use of the term genocide as such acknowledgement would have required an intervention from those who had signed the Genocide Convention. 46 As for Serbia, a draft resolutionrecognizing genocide-was introduced in 2005 but the Serbian Parliament did not adopt it. 47 In 2010, it acknowledged that a "crime" and a "tragedy" had occurred in Srebrenica but never referred to it as genocide.…”
Section: Interpretative Denial In Bih (And Beyond)mentioning
confidence: 99%
“…58 Cushman explains that this relativism, among other factors, has been fuelling both the denial of Serbian culpability for the crimes that occurred during the 1990's as well as the intensification of Serbian victimhood. 59 Edina Bećirević underlines that "idea linkage distortion and time-sequence confusion" is a method of denial often used by individuals who point out genocide against Serbs during WWII to justify the atrocities carried out in BiH in the 1990's. 60 The author adds that those who disseminate this perspective disregard, among other facts, that both Bosniaks and Croats (and others, such as Jews) were "victims of WWII-era genocidal policies" adopted by certain Serbs.…”
Section: Interpretative Denial In Bih (And Beyond)mentioning
confidence: 99%
“…The sociology of knowledge is not a usual complement to political science and international relations theory. Yet it is clear that particular types of knowledge about the Balkan wars, as argued in the case of the Yugoslavian conflicts, 2 had a decisive and independent influence on the outcomes of the wars as well as on the international representations of Southeast Europe. The task of any sociology of knowledge is not to deny the possibility of absolute truth, but as Karl Mannheim insisted, to increase the possibility of objectivity in the pursuit of knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…132 Indeed, these representations guided much of West European understanding of the Yugoslav conflicts and legitimated the international political choices of inaction, such as indifference and non-intervention to prevent genocide in Southeast Europe. 133 More specifically, the reduction of collective memory to an essentialist core and the elevation of nationalism to the status of a mystical causal agent make it difficult to break free from the conceptual framework of primordial, timeless and unchanging ethno-religious hatred, violence and atrocities. The relativism of this conceptual framework 'distracts the reader from examining relevant evidence' , 134 which may warrant different, more critical and more politically informed interrogations.…”
mentioning
confidence: 99%